Maternal, neonatal and children´s health in Sub-Saharan East Africa - Donát, Josef (Clinical Journal of Obstetrics and Gynecology, 2020)
The Czech model for reducing maternal and neonatal mortality for countries in sub-Saharan East Africa was created on the basis of the Archdiocesan Charity Prague project for a specific region-subcounty Buikwe, Diocese of Lugazi, Mukono Region in Uganda, a region with about 30,000 inhabitants. The aim of the first phase of the project was to build a new hospital, equip it completely for obstetric and surgical operations from the Czech Republic, ensure its activities with Czech and Slovak doctors experts, junior Ugandan doctors and Ugandan medical staff, provide obstetric training for villagers, ensure connections with villages and possibility of fast transport and urgent solution of all acute pathologies in the hospital, capable of 24-hour surgical readiness. In the second phase of the project, a school for midwifery was to be established. This second part of the project has not yet been implemented. The project could serve as an example and guide for similar humanitarian activities in other regions of Uganda and other countries in equatorial Africa.